Dinámica de la latencia en semillas de Brachiaria dictyoneura (Fig & Not) stapf cv llanero - López Y.; Ferguson J. E.; Sánchez Manuel Salvador (Acta Agronómica)
Samples of five commercial seed lots B. dictyoneura from Colombia, Panama and Costa Rica of identical age were studied in a series of laboratory trials. To characterice the physical and physiological dormancy as well as its dynamics in time. Complete spikelets, spikelets scarified with sulfuric acid during 30 minutes, an naked caryopses of each sample were exposed to treatments as follows: 1. Application of different dry-heat regimes with three temperature levels (ambient, 40 and 6CJ>C) and three times (0, 72 and 240 hours), at 1 and 3 months after harvest. 2. Application of Gelvatol in combination with hydration, dehydration, potassium nitrate application, and low temperature treatment. The Gelvatol treatment was compared with an application of a 0,2% potassium nitrate solution; the control treatment was water. The seed dormancy is high and persistent even eleven months post harvest. Two forms o f seed dormancy could be detected, one physiological, the other physical associated with external coats of seeds. The physiological form is minimal at three months while physical form is high even six months after harvest. Complete spikelets maintened a high level of dormancy (73-83%) even eleven months after harvest. Application of Gelvatol and potassium nitrate reduced dormancy of seeds only nine months after harvest. In contrast, acid-scarified spikekelets showed a progressive decrease of dormancy with time, reaching a minimum value at six months after harvest. Dry heat, particularly 60°C improved Normal Germination until six months after harvest. After six months the dry-heat regimes were similar to acid scarification only. En cinco muestras de semillas de B. dictyoneura cosechadas en la misma época en Colombia, Panamá y Costa Rica, se evaluó el efecto de tres niveles de calor seco (ambiente, 40 y 60°C) y tres tiempos de exposición (0, 72 y 240 h) aplicados a uno y tres meses poscosecha en espiguillas completas o escarificadas (30 minutos en ácido sulfúrico) y a cariópsides libres. En otro experimento se evaluó el efecto del tratamiento con Gelvatol y Nitrato de Potasio. Se utilizó un diseño completamente al azar y se efectuaron evaluaciones a uno, tres, seis y nueve meses pos-cosecha (mpc). La latencia fue alta y persistió hasta los doce mpc y presenta dos componentes: uno fisiológico debido al embrión y otro físico asociado con cubiertas de la semilla; el fisiológico fue mínimo a los 3 meses, y el físico fue alto hasta los 6 mpc. Las espiguillas completas mantuvieron niveles de latencia altos (73-83%) hasta los nueve mpc. El Gelvatol y el Nitrato de Potasio fueron efectivos contra la latencia de las espiguillas completas, solamente después de los nueve mpc. Las espiguillas escarificadas presentaron el valor mínimo a los 6 mpc. Los mejores tratamientos contra la latencia, hasta los 6 mpc, en las espiguillas escarificadas fueron la exposición a 40°C durante 72 y 240 horas. Después de los 6 mpc los tratamientos con calor no presentaron efecto diferente al obtenido con la escarificación con ácido sulfúrico.